Surgical management of unilateral gangrenous mastitis in a doe: A case report (Journal of Advanced Veterinary and Animal Research, 2015)
A case of gangrenous mastitis was surgically manageed in a cross breed doe aging 3.5 years and weighing 25 kg at SA Quadery Teaching Veterinary Hospital of Chittagong Veterinary and Animal Sciences University, Chittagong, Bangladesh. Confirmatory diagnosis of the case was done based on physical changes of udder, and identification of associated bacterial agents; two bacteria namely Staphylococcus aureus and Escherichia coli could be isolated from the milk sample. Parenteral administration of combined antimicrobials (Gentamycin + Sulphadimidine + Trimethoprim) and concurrent intra-mammary infusion of antimicrobials (Streptomycin + Penicillin) along with supportive treatments for 7 days could not save the quarter rather the condition deteriorated. After performing the antibiogram of the isolated bacteria, only Ciprofloxacin was found to be sensitive. Mastectomy was done, and Ciprofloxacin (dosed at 10 mg/kg body weight) was given intramuscularly as antimicrobial, together with supportive medicine. The doe recovered without any complication after 7 days of post-treatment and managementhttp://dx.doi.org/10.5455/javar.2015.b75